Morphometric Similarity Patterning of Amyloid-β and Tau Proteins Correlates with Transcriptomics in the Alzheimer’s Disease Continuum - Brusini, Lorenza; Dolci, Giorgio; Pini, Lorenzo; Cruciani, Federica; Pizzagalli, Fabrizio; Provero, Paolo; Menegaz, Gloria; Boscolo Galazzo, Ilaria (International journal of molecular sciences, 2024)
Bridging the gap between cortical morphometric remodeling and gene expression can help to clarify the effects of the selective brain accumulation of Amyloid-β (Aβ) and tau proteins occurring in the Alzheimer’s disease (AD). To this aim, we derived morphometric similarity (MS) networks from 126 Aβ- and tau-positive (Aβ+/tau+) and 172 Aβ−/tau− subjects, and we investigated the association between group-wise regional MS differences and transcriptional correlates thanks to an imaging transcriptomics approach grounded in the Allen Human Brain Atlas (AHBA). The expressed gene with the highest correlation with MS alterations was BCHE, a gene related to Aβ homeostasis. In addition, notably, among the most promising results derived from the enrichment analysis, we found the immune response to be a biological process and astrocytes, microglia, and oligodendrocyte precursors for the cell types. In summary, by relating cortical MS and AHBA-derived transcriptomics, we were able to retrieve findings suggesting the biological mechanisms underlying the Aβ- and tau- induced cortical MS alterations in the AD continuum.